2008
DOI: 10.4049/jimmunol.181.8.5204
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: CD47 Controls the In Vivo Proliferation and Homeostasis of Peripheral CD4+CD25+Foxp3+ Regulatory T Cells That Express CD103

Abstract: Peripheral CD103+Foxp3+ regulatory T cells (Tregs) can develop both from conventional naive T cells upon cognate Ag delivery under tolerogenic conditions and from thymic-derived, expanded/differentiated natural Tregs. We here show that CD47 expression, a marker of self on hematopoietic cells, selectively regulated CD103+Foxp3+ Treg homeostasis at the steady state. First, the proportion of effector/memory-like (CD44highCD62Llow) CD103+Foxp3+ Tregs rapidly augmented with age in CD47-deficient mice (CD47−/−) as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 29 publications
(29 reference statements)
4
25
0
Order By: Relevance
“…TCR transgenic mice were at least as efficient as those from CD47-sufficient mice at inhibiting CD4 T cell proliferation, monitored by the extent of CFSE dilution. These results support previous findings demonstrating that neither the quantity nor the function of Tregs is reduced in CD47-deficient non-transgenic mice [42]. Rather, Tregs appear to slowly accumulate with age in CD47-deficient mice [42].…”
Section: Tregs Cd4 and Cd8 T Cells Are Not Influenced By The Absencesupporting
confidence: 93%
See 1 more Smart Citation
“…TCR transgenic mice were at least as efficient as those from CD47-sufficient mice at inhibiting CD4 T cell proliferation, monitored by the extent of CFSE dilution. These results support previous findings demonstrating that neither the quantity nor the function of Tregs is reduced in CD47-deficient non-transgenic mice [42]. Rather, Tregs appear to slowly accumulate with age in CD47-deficient mice [42].…”
Section: Tregs Cd4 and Cd8 T Cells Are Not Influenced By The Absencesupporting
confidence: 93%
“…These results support previous findings demonstrating that neither the quantity nor the function of Tregs is reduced in CD47-deficient non-transgenic mice [42]. Rather, Tregs appear to slowly accumulate with age in CD47-deficient mice [42]. Together, these data suggest that the increased susceptibility to autoimmune diabetes in CD47-deficient mice cannot be attributed to a defect in Treg homeostasis or function.…”
Section: Tregs Cd4 and Cd8 T Cells Are Not Influenced By The Absencesupporting
confidence: 91%
“…Rather, expression of aEb7 by dendritic cells was found to be necessary for Treg function (see below). Van et al [106] showed that CD47 controls the in vivo proliferation and homeostasis of the aEb7 expressing subset of peripheral Tregs. There is also evidence that aEb7 expressing CD8 T cells can be suppressive.…”
Section: T Regulatory Cellsmentioning
confidence: 99%
“…On the basis of this experience and our validation of SNARF-1 as a T cell proliferation tracking dye, we went on to develop a suppression assay that would allow the simultaneous measurement of both Treg and Tcon proliferation. Thus, CFSE-stained Tregs were found to mediate potent suppression and apoptosis of SNARF-1-stained Tcons in vitro and underwent proliferation themselves when present in co-cultures with Tcons, despite being anergic when cultured alone; in this regard, the assay recapitulated the propensity of Tregs to proliferate in vivo [48,49]. The Treg proliferation was titratable, increasing with increasing numbers of co-cultured Tcons: we speculate that Tcon-derived growth factors, including IL-2 and other ␥ c cytokines, were able to break the anergy of the Tregs in co-culture.…”
Section: Discussionmentioning
confidence: 86%